One-step melt-blowing of multi-scale micro/nano fabric membrane for advanced air-filtration. (28th February 2019) - Deng, Nanping; He, Hongsheng; Yan, Jing; Zhao, Yixia; Ben Ticha, Eya; Liu, Yong; Kang, Weimin; Cheng, Bowen
Abstract: In this study, multi-scale micro/nano fibers membrane based on polypropylene and polystyrene were successfully fabricated by one-step melt-blown technique for high performance air filtration. The incompatibility of the used polymers made the viscosity of blended melt fluctuate continuously, resulting in the remarkable diameter difference occurred in prepared fibers. The micro-scale fibers acted as skeleton supports which could improve the permeability of melt-blown nonwovens, and the nano-scale fibers acted as connection props which could increase the surface area/volume ratio to improve the filtration performance by simply varying the composition of precursor solutions. And the obtained nonwovens showed the enhanced filtration efficiency and reduced pressure drop simultaneously, which included high air filtration efficiency of 99.87%, a low pressure drop of 37.73 Pa and a satisfactory quality factor of 0.18 Pa -1 . The successful preparation of micro/nano fibers by the simple one-step method may develop novel filtration and separation materials to reduce air pollution. Graphical abstract: Image 10 Highlights: Multi-scale micro/nano fibers membrane are prepared by melt-blown technique. The formation principle was attributed to different directional "tug of war". Membrane showed enhanced filtration efficiency and reduced pressure drop. Filtration efficiency of 99.87% and pressure drop of 37.73 Pa can be obtained.